Dinamika Massa Air di Sekitar Pulau-Pulau Kecil Terluar (PPKT) Perairan Utara Papua - Dewi Surinati; Corry Corvianawatie, (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Water Mass Dynamics Around the Indonesia’s Outer Small Islands at North Papua Waters. Coastal area of Indonesia’s Outer Islands (PPKT) at North Papua Waters have a huge potential of marine resources which needs to be managed in sustainable ways. In order to make the processes of protection, conservation, rehabilitation, utilization, and enrichment of coastal resources work well, the study about environmental carrying capacity which includes ocean dynamics analysis around PPKT area is needed. Hereby, the study area were including coastal and off shore area of Jiew, Budd, Fani, Bras and Fanildo Island. The measurement of water mass and ocean current was conducted to analyze the impact of regional ocean dynamics to coastal waters of PPKT. This study found the domination of New Guinea Coastal Current (NGCC) at surface layer, the effect of Indonesian throughflow at subsurface layer (100 – 150m depth), and counter current towards northeast which is believed as a part of New Guinea Coastal Under Current (NGCUC) and Equatorial Under Current (EUC). This ocean current system carried South Pacific Subtropical Water (SPSW) noticed by maximum salinity of 35.4 PSU at 150m depth. There are spatial variability of mixed layer depth and slope of T-S curve at the western and eastern part of study area which might be caused by isopycnal mixing. However, the spatial and temporal variability of Sea Surface Temperature at this area is relatively small due to the presence of Western Paicific Warm Water Pool. With the small annual SST variability, strong ocean current and water mass mixing, this area has a potential for the development of marine ecosystem.